A novel clustering of the SOM using rough set - Mohd. Noor Md. Sap, author; Ehan Mohebi, author; Reginol Student Conference on Reserch and Development (2008 : Johor)i (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL